New dictionary of the history of ideas - Horowitz, Maryanne Cline, 1945- ([New York?] : Charles Scribner's Sons, 2005)
"From abolitionism to Zionism, this encyclopedia clarifies the intel lectual history of more than 750 complex ideas of concern to people tod ay. Like its classic predecessor, the Dictionary of the History of Idea s (1973), this new set covers core Western ideas, while expanding its c overage to include the 'global perspectives and gender-inclusive' conce pts that have evolved in the past 30 years. Reader's guides, cross-refe rences, sidebars, and an index aid the reader in understanding the way ideas combine with other ideas."--"Reference that rocks," American Libr aries, May 2005.
Includes bibliographical references and index.
Keywords: Civilization -- History -- Dictionaries; Intellectual life -- History -- Dictionaries